Epileptic Encephalopathies, CDKL5 Mutations, and Infantile Spasms - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at the Mayo Clinic, Rochester, MN performed retrospective chart reviews of 6 children with epilepsy and CDKL5 mutations.